Jump to content

Dhamnekar Win,odd

Senior Members
  • Posts

    171
  • Joined

  • Last visited

Everything posted by Dhamnekar Win,odd

  1. I am working on question (d) for answering it. Any chemistry help will be accepted. Do you know the correct answer for question(d)?
  2. Whichever and whatever computations of Kc you use, eventually, final answer would be 0.17 mol /L SO2 should be added to the existing 0.2 mol/L SO2.
  3. My corrected answer to (c) is [math] \frac{[1.6]^2}{[ 0.3 - 0.1 + x]^2 [0.20 - 0.05]}=125 \Rightarrow x = 0.17 [/math] mol SO2. ∴(0.17 mol SO2/L) (10 L)= 1.7 mol of SO2.
  4. Please visit here
  5. Yes, I forgot to square the concentration of SO3 in the numerator and the concentration of SO2 in the denominator of the fraction in (b). But R.H.S. 125 is correctly computed. But what is your opinion about my answer to (c)?
  6. Are there any badges here for members?
  7. Are these above answers correct? specifically last one (c)?
  8. a) In how many parts, we can divide an infinite plane by n straight lines of which no two lines are parallel and no three lines are concurrent? b) In how many parts, we can divide an infinite space by n planes of which no four planes meets in a point and no two planes are parallel? How to answer both these questions? What are the answers to these questions? I am working on these questions. Any math help, problem solving hint will be accepted.
  9. Thanks for your reply. I am working on the question 9 and statement in your reply to prove it practically as well as theoretically.
  10. I know the answer to question 8. But how to answer question 9.
  11. I tag this question as "SOLVED"
  12. So, Eventually I did it. Using formula (1) we get [math] A(4,2)= \displaystyle\sum_{k=1}^{3}\binom{4}{k}\cdot \displaystyle\sum_{v=0}^{1}(-1)^v\cdot \binom{1}{v}\cdot (1-v)^{4-k}=14[/math] Using formula (1)we get[math] A(4,3)=\displaystyle\sum_{k=1}^{2}\binom{4}{k}\cdot\displaystyle\sum_{v=0}^{2}(-1)^v\cdot \binom{2}{v} \cdot (2-v)^{4-k}=36[/math] Using formula (2) we get [math]A(4,2)=\displaystyle\sum_{v=0}^{2}(-1)^v \cdot \binom{2}{v}\cdot (2-v)^{4}=14[/math] as expected Using formula (2) we get [math] A(4,3)=\displaystyle\sum_{v=0}^{3}(-1)^v\cdot \binom{3}{v}\cdot(3-v)^{4}=36 [/math] as expected. Thanks for your guidance.
  13. But as per formula (2)r=4 and k=1 , which results in [math] (-1)^0 \cdot \binom{2}{0}\cdot(2-v)^3[/math] Formula (2) = [math]A(r-k,n) =\displaystyle\sum_{v=0}^{n}(-1)^v\binom{n}{v}(n-v)^{r-k}[/math]
  14. So, for [math] k=1, A(3,2)=(-1)^0 \cdot \binom{2}{0} \cdot (2-v)^{4-1=3}[/math] Is this correct?
  15. This answer refers to r=4 objects and n=2 cells question. We know A(r,n) =A(4,2)= 14 , My answer to A(r-k,n))=A(4-k, 2)=7 Is this answer correct?
  16. [math]A(4-k,2)= (-1)^0 \cdot \binom{2}{0} \cdot(2-0)^{4-1} + (-1)^1\cdot \binom{2}{1} \cdot(2-1)^{4-2} = 8-1 =7[/math] Is this answer correct?
  17. My attempt to derive general formula for A(r,n) =[math]\displaystyle\sum_{k=1}^{r-1}\binom{r-1}{k}\cdot A(r-k-1,n-1)[/math]
  18. Author said to change order of summation and use binomial formula to express A(r, n+1) as the difference of two simple sums. So, I did it. As regards derivation of equation(1) using combinatorial arguments, author didn't write anything about that in his book. So, I don't know how to derive it.
  19. If I put r=2, I get answer=3. If I put 4=3, I get answer=7. If I put r=4, I get answer=15. Now what is your suggestion?
  20. I changed the order of summation and the expressed A(4,1+1=2)as the difference of two simple sums [math]\displaystyle\sum_{k=1}^{4}\binom{4}{k} \cdot\displaystyle\sum_{v=0}^{1}(-1)^v\cdot \binom{1}{v}\cdot(1-v)^{4-k}-\displaystyle\sum_{v=0}^{1}(-1)^v\cdot \binom{1}{v}\cdot(1-v)[/math] Now, what we can do?
  21. That's what the author want to suggest. How can we change the order of summations in the answer which we got using formula (1) so that we get the answer 14?
  22. Using formula (2), we get [math] A(4,2)= \displaystyle\sum_{v=0}^{2}(-1)^v\cdot \binom{2}{v}(2-v)^4=14[/math] Using formula (1), we get [math]A(4,2)=\displaystyle\sum_{k=1}^{4} \binom{4}{k}\cdot\displaystyle\sum_{v=0}^{1}(-1)^v \binom{1}{v}(1-v)^{4-k}=15[/math] Now, how can we remove the difference of one between these two answers?
  23. I am trying to derive the formula (1) by combinatorial argument, but I didn't succeed. My difficulty to understand the Author's suggestions: 1) This is a classical occupancy problem. Assuming that all [math]n^r[/math] possible placements are equally probable, the probability to obtain the given occupancy numbers [math]r_1,...r_n[/math] equals [math] \frac{r!}{r_1! r_2!...r_n!} n^{-r}[/math] Here, we are concerned with only indistinguishable particles or objects. In Physics, this probability is known as Maxwell-Boltzmann statistics. Now, suppose, we have to put 4 objects in 2 cells. The number of distinguishable distributions of 4 identical objects into 2 cells is [math]\binom{3}{1}=3[/math].|***|*|, |*|***| or |**|**| But if we use formula (2) we get 14 as answer |**|**|, |**|**|, |**|**|, |**|**|, |**|**|, |**|**|, |***|*|,|***|*|,|***|*|, |***|*|, |*|***|, |*|***|, |*|***|, |*|***| . In case of A,B,C,D objects, we get |AB|CD|,|AC|BD|,|AD|BC|,|BC|AD|,|BD|AC|,|CD|AC|,|ABC|D|,|ACD|B|,|ABD|C|,|BCD|A|,|A|BCD|,|B|ACD|,|C|ABD|,|D|ABC| Using formula (1), we get [math]A(4,3)=\displaystyle\sum_{k=1}^{4}\binom{4}{k}*\displaystyle\sum_{v=0}^{2}(-1)^v*\binom{2}{v}*(2-v)^{4-k}=35[/math] I think this answer assumes distinguishable cells as well as objects. Now I don't understand , on what basis , we can say that this formula is derived assuming indistinguishable objects?
×
×
  • Create New...

Important Information

We have placed cookies on your device to help make this website better. You can adjust your cookie settings, otherwise we'll assume you're okay to continue.